2021
DOI: 10.1016/j.ijid.2021.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on vasooclusive crisis in patients with sickle cell anaemia

Abstract: Objectives The aim of this study was to assess the impact of COVID-19 on the morbidity and mortality on vasooclusive crisis (VOC) in sickle cell anaemia (SCA) patients. Methods One hundred patients with(fifty) or without COVID-19 PCR positivity(fifty), were enrolled in a prospective cohort study after signing a written informed consent. Results The COVID-19 positive patients had significantly higher median VOC episodes/year i.e 3 /year (IQR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Similarly, Alkindi et al 14 reported COVID-19 infection may have triggered the onset of VOC, but it did not significantly influence the morbidity or mortality of SCD patients. The Bronx was disproportionally impacted by the first wave of COVID-19 with more hospitalizations and deaths than any other NYC borough, 15 which may explain the high mortality (11%) in our non-SCD population.…”
mentioning
confidence: 88%
“…Similarly, Alkindi et al 14 reported COVID-19 infection may have triggered the onset of VOC, but it did not significantly influence the morbidity or mortality of SCD patients. The Bronx was disproportionally impacted by the first wave of COVID-19 with more hospitalizations and deaths than any other NYC borough, 15 which may explain the high mortality (11%) in our non-SCD population.…”
mentioning
confidence: 88%
“…with COVID-19 required admission to the ICU. n/a n/a n/a n/a Alkindi et al [ 26 ] Oman 50 (27/23) 31 HbSS (10), HbSβ 0 (29), Unknown (11) BT (26) SCD w/o COVID-19 Although COVID-19 may trigger VOC onset, it does not increase mortality compared to non-COVID-19 pts. with VOC.…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%
“…Adult SCD patients typically experience mild to moderate COVID-19-related symptoms [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], which is characterized by few respiratory symptoms and not requiring intensive care unit (ICU) admission. Large US registry studies found that approximately 80% of adult SCD patients experience mild to moderate symptoms (or no symptoms at all) [ 29 , 30 ] and that the type of COVID-19-related symptoms, including cough/fever or more severe symptoms such as respiratory failure, were not different from patients without SCD [ 33 ].…”
Section: Patients With Covid-19 and Sickle Cell Diseasementioning
confidence: 99%
“…It is also important to note that although mortality in patients with SCD who had COVID-19 was slightly higher than that of the general population, our own experience with COVID-19 related illness in SCD was generally of a mild to moderate in severity. 7 …”
Section: Discussionmentioning
confidence: 99%